MEKANISME PENSINYALAN VASCULAR ENDOTHELIAL GROWTH FACTOR DALAM PERKEMBANGAN DAN PENYEBARAN KANKER - Liana, Nana; Helmizar, Roland; Ruhsyahadati, Ruhsyahadati; Triyana, Rahma; Saputra, Muhammad Rizki (Yayasan Nusantara Hasana Berdikari, 2025)
Vascular Endothelial Growth Factor (VEGF) is a key mediator in the process of angiogenesis, playing a crucial role in the development and spread of malignant tumors. VEGF consists of several isoforms, primarily VEGF-A, which exert their effects through receptors VEGFR-1, VEGFR-2, and VEGFR-3, as well as co-receptors neuropilin-1 and -2. Activation of VEGF signaling pathways stimulates endothelial cell proliferation, migration, and survival, increases vascular permeability, and facilitates the formation and invasion of tumor-associated blood vessels. VEGF expression is regulated by various factors, including hypoxia via HIF-1α activation, oncogenes such as KRAS and Src, and the suppression of tumor suppressor genes such as p53 and PTEN. Additionally, several growth factors including EGF, PDGF, and IGF contribute to the regulation of VEGF. VEGF signaling also promotes tumor invasion by activating proteolytic enzymes such as MMP-2, MMP-9, and uPA, which degrade the basement membrane. Due to its central role in angiogenesis and tumor invasion, VEGF is a strategic target in anti-angiogenic therapies for various types of cancer. A comprehensive understanding of the structure, function, and regulation of VEGF is essential for the development of more effective molecular therapies.